Relationship between employer branding and talent retention in company A (automation and engineering company) - Chung, Davis Boon Poh (2010)
The purpose of this research is to examine the relationship between employer branding and talent retention. The respondents of this research were 100 employees of company A from executive level and above. Specifically, the purpose of this study was to: (1) identify the perception of employees towards employer branding and talent retention; (2) examine the relationship between employer branding and talent retention; (3) examine the relationship between employer branding and talent commitment; (4) to identify the relationship between employer branding and talent engagement and involvement; (5) to identify the relationship between employer branding and talent training and career development; (6) to examine the relationship between employer branding and talent valuing and (7) to examine the impact of employer branding and talent retention. The survey method was used whereby a set of questionnaires was distributed to gather data and it was analyzed using the quantitative method descriptive and inferential statistics in order to achieve the research objectives. The result of the research shows that the average means score of respondents’ perception toward employer branding and talent retention were; employer branding; brand association- 3.636, brand identity- 3.65, brand culture- 3.602, brand loyalty / commitment– 3.39, brand psychological contract – 3.601. Talent retention; talent employee commitment – 3.44, talent engagement and involvement – 3.60, talent training and career development – 3.34, talent valuing – 3.33. The result also showed that there was a high and positive relationship (r =0.825) between employer branding and talent retention and it supported hypothesis H1 at 0.05 level. There was also moderate and positive relationship between employer branding and talent employee commitment which is significant at level 0.05 (r = 0.640) and which also supported H2. The results also showed that there was moderate and positive relationship (r = 0.693) between employer branding and talent employee engagement and involvement and it supported hypothesis H3 at 0.05 level. There was moderate and positive relationship between employer branding and talent training and career development which is significant at level 0.05 (r = 0.689) which supported H4. There was high and positive relationship between employer branding and talent valuing is significant at level 0.05 (r = 0.790) which supported H5. Lastly the analysis result of multiple regressions showed that employer branding has a significant relationship on talent retention (F= 7.32913) and is significant at level 0.05 which supported H6. The value of adjusted R Square proves that brand association, brand identity, brand culture, brand loyalty / commitment and brand psychological contract have influenced as much as 67.5% on talent retention. Results of multiple regression analysis also revealed that brand culture is the main contributor to the impact on the talent retention (ß = 0.261) and it is significant at level 0.05.